Three-year clinical performance of direct restorations using low-shrinkage Giomer vs. nano-hybrid resin composite - Toz-Akalin, Tugba; Öztürk-Bozkurt, Funda; Kusdemir, Mahmut; Özsoy, Alev; Yüzbaşıoğlu, Emir; Özcan, Mutlu (Frontiers in Dental Medicine, 2024)
Objectives The objective of this investigation was to compare the clinical performance of a nano-hybrid resin composite and a low-shrinkage Giomer resin composite. Material and methods In total, 35 pairs of restorations were performed using either low-shrinkage Giomer (Beautifil II LS, Shofu Inc.) or nano-hybrid (Clearfil Majesty Posterior) resin composite in 35 patients by two operators using the relevant adhesives, i.e., FL-Bond II (Shofu Inc.) and Clearfil SE Bond (Kuraray), with the self-etching technique according to each manufacturer's instructions. Two clinicians assessed the restorations 2 weeks (baseline); 6 months; and 1, 2, and 3 years after the restorative procedures using FDI (World Dental Federation) criteria (Scores 1–5). Data were analyzed using the marginal homogeneity and McNemar tests. The survival rate was calculated using Kaplan–Meier survival analysis and the survival of the two groups was compared with the log-rank test (p = 0.05). Results The mean observation period was 37.7 ± 6.8 months. All restorations completed their 3-year follow-up. The criteria were mainly rated with high (1 or 2) scores for quality in both groups. Only one restoration in the low-shrinkage Giomer resin composite group was accepted as a failure at the 2-year recall due to retention loss. Conclusion At the 3-year follow-up, the performance of the restorations using the Giomer and the nano-hybrid resin composite were similar and clinically acceptable. Clinical relevance The low-shrinkage Giomer resin composite exhibited a similar clinical performance to the nano-hybrid resin composite after 3 years in service with both materials displaying minor surface deteriorations at the 3-year recall. Clinical Trial Registration https://clinicaltrials.gov, identifier: NCT02823769.